Efficient algorithms for agent-based semantic resource discovery - Lopes, A. L. (2012)
A semantic overlay network is a powerful mechanism for collaborative environments where multiple agents, managing several resources, can cooperate in pursuing common and individual goals while achieving good overall performance. However, building such a social structure dynamically from an unstructured peer-to-peer network is a lengthy process if appropriate algorithms and techniques are not used. In this paper, we analyse a set of network evolution techniques that improve the performance of classic approaches, such as the flooding search algorithm. We compare the efficiency of these enhanced classic algorithms with our previously proposed search algorithm, which has also been improved through the referred techniques. Evaluation tests show that the improved version of our algorithm outperforms the improved version of the classic search algorithm and efficiently creates a semantic overlay network for agent-based resource coordination.